Construction of a versatile SNP array for pyramiding useful genes of rice. (January 2016) - Kurokawa, Yusuke; Noda, Tomonori; Yamagata, Yoshiyuki; Angeles-Shim, Rosalyn; Sunohara, Hidehiko; Uehara, Kanako; Furuta, Tomoyuki; Nagai, Keisuke; Jena, Kshirod Kumar; Yasui, Hideshi; Yoshimura, Atsushi; Ashikari, Motoyuki; et al.
Highlights: SNPs of 31 rice varieties were collected using Affymetrix 44K Rice SNP microarray. Haplotypes of 14 known useful genes were converted to Illumina Golden Gate array. The accuracy of the custom array was confirmed by using 3 F2 populations. The haplotype-based selection facilitates gene pyramiding in rice breeding. Abstract: DNA marker-assisted selection (MAS) has become an indispensable component of breeding. Single nucleotide polymorphisms (SNP) are the most frequent polymorphism in the rice genome. However, SNP markers are not readily employed in MAS because of limitations in genotyping platforms. Here the authors report a Golden Gate SNP array that targets specific genes controlling yield-related traits and biotic stress resistance in rice. As a first step, the SNP genotypes were surveyed in 31 parental varieties using the Affymetrix Rice 44K SNP microarray. The haplotype information for 16 target genes was then converted to the Golden Gate platform with 143-plex markers. Haplotypes for the 14 useful allele are unique and can discriminate among all other varieties. The genotyping consistency between the Affymetrix microarray and the Golden Gate array was 92.8%, and the accuracy of the Golden Gate array was confirmed in 3 F2 segregating populations. The concept of the haplotype-based selection by using the constructed SNP array was proofed.